Tweak and cIAP1 Mediate Alternative NF-κB Signalling to Promote Myogenesis - Adam, Nadine Jessica (Université d'Ottawa / University of Ottawa, 2016)
The NF-κB family of transcription factors can be activated through canonical (classical) or non-canonical (alternative) signalling pathways, which are regulated by the redundant ubiquitin ligases, cellular inhibitor of apoptosis 1 and 2 (cIAP1 and cIAP2). While the canonical NF-κB pathway is needed for myoblast proliferation, it is inactivated during myoblast differentiation. However, the non-canonical NF-κB pathway is a major factor in promoting myoblast fusion, which is crucial to the processes of myogenesis and muscle repair. Ablation of cIAP1 levels through a chemical antagonist such as a SMAC- mimetic compound (SMC) activates non-canonical signalling to enhance myogenesis. The cytokine TNF-like weak inducer of apoptosis (TWEAK) has also been shown to activate primarily the alternative NF-κB pathway when signalling through its receptor Fn14. Here I show that alternative NF-κB signalling activity, stimulated by the addition of TWEAK or loss of cIAP1, can promote myogenesis. I also demonstrate that TWEAK is an endogenous myokine produced by myoblasts to promote their own differentiation, and suggest that targeting the alternative NF-κB pathway, with SMAC-mimetics or recombinant TWEAK for example, would be of therapeutic value in the repair and regeneration of muscle for various myopathies.
Keywords: myogenesis; NF-κB signalling; cellular inhibitors of apoptosis (cIAPs); TNF-like weak inducer of apoptosis (TWEAK); myoblast fusion; myoblast differentiation; smac-mimetic compounds